Pengaruh Formulasi Ekstrak Biji Ketumbar (Coriandrum Sativum) sebagai Repellent Nyamuk Aedes Sp - Nazilia Rizqi Fitriani; Sri Muryani; S. Eko Windarso (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2019)
Abstract: Effect of Coriander Seed Extract Formulation ( Coriandrum sativum) as Repellent to Mosquito Aedes sp. Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. Vector control of the Aedes mosquito can use natural and safer ways, one of which is by using coriander seeds (Coriandrum sativum). The purpose of this study was to determine the effect of coriander seed extract formulation in the Gel Air Freshener as a repellent against the resistance of Aedes mosquitoes. This type of research is an experiment with a post-test only with control Group Design. The repellent used is made from a mixture of coriander seed extract (Coriandrum sativum) and Gel Air Freshener with 3 formulations. Research sample in the form of Aedes mosquito. the results of egg hatching were obtained from the installation of ovitrap in one of the houses in Jalan Langenastran Kidul as many as 600 for 6 repetitions. The data obtained were analyzed by One Way Anova test at 95% confidence level).Based on the results of the repellent research on Aedes mosquitoes in the amount of 50.7% formulation A, 58.7% formulation B and 62.7% formulation C. The statistical test results showed each value of p = 0,000 (p